2015
DOI: 10.1155/2015/521381
|View full text |Cite
|
Sign up to set email alerts
|

Role of FTO in Adipocyte Development and Function: Recent Insights

Abstract: In 2007, FTO was identified as the first genome-wide association study (GWAS) gene associated with obesity in humans. Since then, various animal models have served to establish the mechanistic basis behind this association. Many earlier studies focussed on FTO's effects on food intake via central mechanisms. Emerging evidence, however, implicates adipose tissue development and function in the causal relationship between perturbations in FTO expression and obesity. The purpose of this mini review is to shed lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 77 publications
(99 reference statements)
0
24
1
Order By: Relevance
“…We did not observe any effects on transcript stability or translational differences in Fto-regulated targets. Contrary to others, we did not find differential splicing of Runx1t1 in response to Fto knockdown (52,89), suggesting that demethylation of m6A RNA in adipocytes may not be Fto's critical function. We identified Cebpb and Cebpd as targets of Fto.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not observe any effects on transcript stability or translational differences in Fto-regulated targets. Contrary to others, we did not find differential splicing of Runx1t1 in response to Fto knockdown (52,89), suggesting that demethylation of m6A RNA in adipocytes may not be Fto's critical function. We identified Cebpb and Cebpd as targets of Fto.…”
Section: Discussioncontrasting
confidence: 99%
“…The FTO gene (MGI: 1347093), encoding the fat mass and obesity‐associated protein, was the first GWAS‐identified obesity and obesity‐related trait‐associated gene (ie, type 2 diabetes, hip circumference, bodyweight index, bodyweight) . Owing to the various studies of FTO association with obesity and obesity‐related phenotypes, it is now evident that FTO is highly expressed in adipose tissues, playing a crucial role in adipogenesis (cross‐talk with Irx3 ) and extremely involved in early development, and yet its function is still obscure beyond the adipose tissue . In relevance to liver weight phenotype, studies of FTO homozygous, null mice reported postnatal growth retardation accompanied by decreased bodyweight (lean and fat weight), suggesting the complex and major role of FTO in body development and composition, whether independently or by co‐regulatory mechanisms with the Irx B cluster and Rpgrip 1l gene .…”
Section: Resultsmentioning
confidence: 99%
“…The association between genetic variants within the fat mass and obesity-associated ( FTO ) gene and metabolic syndrome is widely reported [ 68 ]. FTO encodes an alpha-ketoglutarate-dependent dioxygenase, which plays a role in adipocyte development and function [ 69 ]. Three SNPs within the FTO gene were studied for GDM.…”
Section: Single-nucleotide Polymorphismsmentioning
confidence: 99%